Changes in general practitioners' attitudes toward COVID-19 vaccination after first interim results: a longitudinal approach in France - Pierre Verger; Dimitri Scronias (Taylor & Francis Group, 2021)
We assessed whether the a priori acceptance by French general practitioners (GPs) of COVID-19 vaccines changed after the announcements about them in November 2020. In all, between two surveys in October-November and in November-December 2020, acceptance of COVID-19 vaccines increased among 16.9% of GPs and decreased among 23.0%. Among those with high acceptance in October-November (52.5%), 11.6% became hesitant-reluctant in November-December; in those with initial hesitancy-reluctance (24.6%), 15.2% showed high acceptance. Deteriorating acceptance was significantly associated with GPs' distrust in the Ministry of Health and a priori concerns about the safety of vaccines developed during an epidemic; the reverse was found for improving acceptance. In addition, better acceptance was more likely among GPs who perceived the medical severity of COVID-19 to be high and was less common among women. During a severe pandemic, GPs' trust in health institutions and perception of safety issues remain important predictors of their attitudes toward new vaccines. Vigilance is needed regarding health professionals' reactions to events that may cast doubt on the safety or efficacy of certain COVID-19 vaccines. Personalized approaches should be considered and tested to address their concerns as the situation and knowledge evolve.